2017
DOI: 10.1136/bmjsem-2017-000239
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of laceration injuries in professional and amateur rugby union: a systematic review and meta-analysis

Abstract: BackgroundStudded footwear can cause severe lacerations in rugby union; the prevalence of these injuries is currently unknown.ObjectiveTo summarise the skin and laceration injury prevalence in published epidemiological studies and to investigate any differences in skin injury risk between amateur and professional players.DesignSystematic literature review and meta-analysis of epidemiological studies.Data sourcesPubMed, Web of Science, Scopus and Ovid.Eligibility criteria for selecting studiesProspective, epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The rate of laceration injuries [27] is much higher among male players than among female players (over 2.7 times as high when compared across all age groups), which may indicate differences between the genders in the perceived acceptability of intentional acts of illegal play such as striking, kicking or trampling on opponents, and/or a more aggressive approach in going into contact situations. Although male players had higher rates of injuries to all body regions when considered across all age groups, the differences were greater for injuries to the shoulder and head/face and smaller for injuries to the knee and ankle.…”
Section: Injury Epidemiologymentioning
confidence: 99%
“…The rate of laceration injuries [27] is much higher among male players than among female players (over 2.7 times as high when compared across all age groups), which may indicate differences between the genders in the perceived acceptability of intentional acts of illegal play such as striking, kicking or trampling on opponents, and/or a more aggressive approach in going into contact situations. Although male players had higher rates of injuries to all body regions when considered across all age groups, the differences were greater for injuries to the shoulder and head/face and smaller for injuries to the knee and ankle.…”
Section: Injury Epidemiologymentioning
confidence: 99%
“…The dermatologic disorders that may develop in athletes can be a direct consequence of the actions involved by the participant or an indirect sequelae of infection or allergy. Similar to our patient with pull-up palms, the designation of specific sports-associated dermatosis has been created by linking the athletic activity and the affected location [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…They include not only infections, but also dermatoses from trauma and contact allergies. Several sports have unique skin conditions that may be observed in participants [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey study found that 71% of rugby players have received a laceration injury caused by a rugby stud resulting in them having to leave the field of play [2]. Although laceration and skin injury is generally uncommon in Rugby Union, (approximately 5% of the total incidence of all injuries [3]) players will frequently require stitching and be exposed to infections [4,5]. There is, therefore, a potential benefit of wearing padded clothing if its ability to prevent these types of injuries can be proven.…”
Section: Introductionmentioning
confidence: 99%